F Pencarian File Pada Arsip Karyawan Menggunakan Algoritma Sequential Search - Melati, Anggun; Oktarina , Dwi; Gusrianty, Gusrianty; Joni Kurniawan, Wahyu (IT Journal Research and Development, 2022)
PT. Jaya Nika Permata Group is one of the companies engaged in the Bakery, Café and Restaurant which has been running for 37 years and is still active until now. Currently based in the city of Pekanbaru, and already has branches in Duri, Dumai, Batam. With the total number of employees of PT. Jaya Nika Permata Group has approximately 485 employees, of course, the number of employee files that will be archived is quite large and the file types are varied. In addition, the process of searching for employee files at the time of archived and when files are needed will take a long time considering the large number of employees. Currently, there is no system that can help facilitate the employee's file archiving activities. In this study, field research was conducted to determine the condition of the current file archiving system. Based on the analysis that has been obtained, research is carried out to develop an employee file filing system that is currently running at PT. Jaya Nika Permata. Searching files in employee archives using a sequential search algorithm is expected to facilitate employee file archiving activities and speed up the process of searching for employee files when needed.